Ansavaricins F–I, new DNA topoisomerase inhibitors produced by Streptomyces sp. S012. Issue 24 (7th March 2017) - Zhang, Zhiqiang; Wu, Xingkang; Song, Rentai; Zhang, Juanli; Wang, Haoxin; Zhu, Jing; Lu, Chunhua; Shen, Yuemao
Abstract : Ansamycins are a family of macrolactams characterized by an aromatic chromophore with an aliphatic chain ( ansa chain) connected back to a nonadjacent position through an amide bond. Abstract : Ansamycins are a family of macrolactams characterized by an aromatic chromophore with an aliphatic chain ( ansa chain) connected back to a nonadjacent position through an amide bond. In this study, four new polyketides of ansamycin class, designated as ansavaricins F–I (1–4 ), were obtained from the Streptomyces sp. S012 strain. All the compounds were structurally characterized as open-chain streptovaricin derivatives by using NMR and HRESIMS techniques, and showed different degrees of inhibition against human DNA topoisomerases. Ansavaricin H is a promising lead for the development of new inhibitors of human DNA topoisomerases.